“Eukairos” and “Akairos” in 2 Timothy 4:2: A Hermeneutical-Theological Study for Gospel Preachers - Aska Aprilano Pattinaja; Andris Kiamani; Chevin Papilaya (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2026)
2 Timothy 4:2 emphasizes two conditions that a preacher of the gospel must face in carrying out his calling, namely